2012
DOI: 10.1186/1741-7015-10-129
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal nicotine exposure induces asthma in second generation offspring

Abstract: BackgroundBy altering specific developmental signaling pathways that are necessary for fetal lung development, perinatal nicotine exposure affects lung growth and differentiation, resulting in the offsprings' predisposition to childhood asthma; peroxisome proliferator-activated receptor gamma (PPARγ) agonists can inhibit this effect. However, whether the perinatal nicotine-induced asthma risk is restricted to nicotine-exposed offspring only; whether it can be transmitted to the next generation; and whether PPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
183
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(198 citation statements)
references
References 53 publications
11
183
1
3
Order By: Relevance
“…Specifically, a number of phenotypes have previously been associated with other models of prenatal nicotine exposure, including those of alterations in behaviour (Klein et al, 2003;Pauly et al, 2004), respiratory function (Rehan et al, 2012), and immune function (Basta et al, 2000). These phenotypes have largely been identified following nicotine exposure either for the entirety of gestation, or late in gestation.…”
Section: Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, a number of phenotypes have previously been associated with other models of prenatal nicotine exposure, including those of alterations in behaviour (Klein et al, 2003;Pauly et al, 2004), respiratory function (Rehan et al, 2012), and immune function (Basta et al, 2000). These phenotypes have largely been identified following nicotine exposure either for the entirety of gestation, or late in gestation.…”
Section: Future Directionsmentioning
confidence: 99%
“…Following in vivo gestational nicotine exposure in rats, the offspring at postnatal day 21 were found to have global changes in the level of DNA methylation (testicular and ovarian tissue), histone 3 acetylation (lung and testicular tissue), and histone 4 acetylation (lung, testicular, and ovarian tissue) (Rehan et al, 2012). Another study identified downregulation of angiotensin type 2 mRNA in male postnatal day 10 rat pups, which was correlated to increased methylation at the promoter region of this gene, following gestational exposure to nicotine (Li et al, 2012).…”
Section: Cellular and Molecular Changes Associated With Prenatal Nicomentioning
confidence: 99%
See 1 more Smart Citation
“…But, similarly to an earlier study extending to F 2 offspring, the effects were sex-specific, with total airway system resistance significantly greater in males than females, due in part to tracheal constriction, which was detected only in males. 5,6 What's still unclear (and a subject of his current research), Rehan says, is whether the transgenerational effect is being carried through the male or female germ line.…”
Section: 4mentioning
confidence: 99%
“…Most of these findings come from rodent studies. 4,5,6,7 But preliminary evidence that chemical effects can carry over generations in humans is also emerging, although no F 3 data have been published yet. Given the challenges of tracking effects over multiple human lifespans, the evidence is more difficult to interpret, particularly with respect to potential mechanisms, says Tessa Roseboom, a professor of early development and health at the Academic Medical Center in Amsterdam, the Netherlands.…”
mentioning
confidence: 99%